Pemantauan Dan Peninjauan Kebijakan Penyelenggaraan Pemerintahan Otonomi Khusus - Riskiyono, Joko (Seminar Nasional Teknologi dan Multidisiplin Ilmu (SEMNASTEKMU), 2025)
The monitoring and review in the policy of implementing the Aceh Government as an evaluation of the peace agreement between the Government of the Republic of Indonesia and the Free Aceh Movement which has been running for 20 (twenty) years, on the implementation of special autonomy, from the conflict that has been torn apart for a long time for three decades to rise and rebuild after Aceh after the Tsunami in order to achieve progress and success. The policies in the implementation and implementation of the current development and services of the Aceh Government are considered to be unable to fully realize and answer the welfare of the community, justice, promotion, fulfillment and protection of human rights based on the principles of good governance. The current practice of government administration, it turns out that in its implementation it is faced with the problem of broad and special authority that cannot be implemented. The authority of the Government of Aceh leaves legal problems that must be adjusted to the provisions of the Government of the Republic of Indonesia related to national norms, standards, procedures and criteria so that they are not in line with the Special Autonomy that applies lex specialist in Aceh. For this reason, the Government of Aceh needs to strengthen the authority that has been handed over not with a heart, so it is necessary to carry out the implementation of monitoring and reviewing policies carried out by observing, recording, and assessing the implementation of the implementation of the Aceh Government, to know the achievement of the planned results, the impact caused, and its benefits for Aceh and the Unitary State of the Republic of Indonesia.